Cultivation of forage maize in boreal conditions : Assessment of trade-offs between increased productivity and environmental impact - Lehtilä, Anniina; Taghizadeh-Toosi, Arezoo; Roitto, Marja; Kokkonen, Tuomo; Mäkelä, Pirjo S.A.; Sairanen, Auvo; Tuomisto, Hanna L. (Elsevier, 2024)
The cultivation of whole crop forage maize (Zea mays L.) for cattle feed has a potential for increased forage yield while reducing nitrogen (N) fertilisation compared to perennial grass-based systems. However, the possible environmental trade-offs of forage maize cultivation remain unknown in the boreal region due to the short growing season which limits cultivation practices. The aim of this study was to compare the environmental impact of forage maize with more widely cultivated forage crops in Finland that include perennial silage grass mixtures and whole crop spring cereal harvested as silage. The use of plastic mulch film in forage maize cultivation was included in the assessment as well. A life cycle assessment (LCA) was conducted including impact categories for global warming potential; marine and freshwater eutrophication; terrestrial acidification; freshwater, marine and terrestrial ecotoxicity; land use; and fossil resource depletion. Additionally, soil organic carbon (SOC) stock changes under long-term cultivation of the studied forage crops were simulated with the C-TOOL and Yasso20 models with methodological comparisons. The only clear differences between the studied crops were that the land use was lower (−26–48%) for forage maize, and the freshwater eutrophication (+59–67%) and terrestrial acidification (+10–57%) were higher for perennial grasses compared with other forages. A risk for decreased SOC stock under continuous forage maize cultivation was observed. Forage maize could be used to supplement perennial grass cultivation without major associated environmental risks. Future research shall be conducted on the effect of forage choices on the environmental impact of boreal dairy milk production and on decreasing the current high uncertainty associated with nitrous oxide (N2O) emission factors and SOC stock modelling choices.
Keywords: Forage maize; Silage grass; Boreal cultivation; Sustainable farming; Soil carbon stock change; Life cycle assessment